(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
This research discuss the fundamental capabilities and the importance of their impact on business organizations and organizational performance. The study of this topic is considered a vital issue in the Iraqi private sector in general and Asia Telecom for communications in particular. Where the researcher designed a questionnaire form consisting of (27) paragraphs for each axis of the research, where the research was applied to a random sample of (25) people of the administrators and accountants in Asia-Cell Telecom in Babylon and Diwaniyah was the problem of the study is increasing competition in the years The results were analyzed using statistical spss using a number of statistical indicators namely, arithmetic mean, standard deviation and relative importance. The regression analysis and the t (t) test were used for The researcher presented a recommendation to the company concerned about the need to pay attention to its resources, especially its human resources with expertise, skills and core competencies as a tool. A strategy to support their organizational performance and develop their knowledge and skills so that they can engage in a competitive war